ISLAMIC ACCOUNTING EDUCATION FOR POSTGRADUATE STUDENTS: THE BENEFITS OF FLIPPED CLASSROOM APPROACH - Nurulhuda Abd Rahman (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The Islamic finance industry significantly supports the development of productive economic sectors such as healthcare, transportation, and green industries, particularly by Islamic social finance instruments. Moreover, the nature of Islamic finance contributes to financial inclusion for underserved populations, aligning with the Sustainable Development Goals. Demand for Islamic fixed-income securities from global investors also has been growing. Therefore, knowledge of Islamic accounting is crucial in preparing students to navigate the unique principles and ethical considerations inherent in Shariah-compliant financial practices and thus fulfil the needs of Islamic finance profession’s talent pool. Traditional teaching methods may not fully engage students or promote a deep understanding of complex, emerging knowledge such as Islamic accounting. Consequently, this article explores the conceptual framework underlying the application of the flipped learning approach in Islamic accounting education at the postgraduate level. It discusses the potential benefits of the flipped learning model and offers recommendations for effectively integrating flipped learning into postgraduate Islamic accounting education.